2020
DOI: 10.1371/journal.pmed.1003319
|View full text |Cite
|
Sign up to set email alerts
|

Economic influences on population health in the United States: Toward policymaking driven by data and evidence

Abstract: • The United States is in the midst of a 40-year-long population health crisis. Life expectancy has declined since 2014, an unprecedented event that has followed on the heels of a decades-long slowing in secular gains in longevity in the US relative to peer countries. These adverse population health trends appear to be primarily driven by worsening health among working-age individuals of lower socioeconomic status. • A growing body of research suggests that worsening economic outcomes-e.g., fading employment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 156 publications
(182 reference statements)
1
30
1
Order By: Relevance
“…This result is not aligned with a study from the United States, for example, that found the probability of missing work was significant across all professional categories for obese women, although among men, the results varied by occupation [ 26 ]. This discrepancy with our findings can by justified due to a much more complex mechanism, including differences in the democracy, as well in the economic situation, labour market and social welfare between Portugal and United States that could be considered as potentially important factor that explaining differences in population health behaviors and consequently in absenteeism [ 27 , 28 ].…”
Section: Discussioncontrasting
confidence: 66%
“…This result is not aligned with a study from the United States, for example, that found the probability of missing work was significant across all professional categories for obese women, although among men, the results varied by occupation [ 26 ]. This discrepancy with our findings can by justified due to a much more complex mechanism, including differences in the democracy, as well in the economic situation, labour market and social welfare between Portugal and United States that could be considered as potentially important factor that explaining differences in population health behaviors and consequently in absenteeism [ 27 , 28 ].…”
Section: Discussioncontrasting
confidence: 66%
“…US research suggests that these largely reflect 'worsening health among working-age individuals of lower socioeconomic status' consistent with evidence that increasing numbers of people are experiencing ever more precarious lives. 28 Our findings are also consistent with evidence from Statistics Canada, 29 which found that while death rates were falling at older ages, at ages 20-44 years, especially among men, they were increasing. This was attributed largely to the opioid crisis which was afflicting several provinces.…”
Section: Discussionsupporting
confidence: 92%
“…US research suggests that these largely reflect ‘worsening health among working-age individuals of lower socioeconomic status’ consistent with evidence that increasing numbers of people are experiencing ever more precarious lives. 28…”
Section: Discussionmentioning
confidence: 99%
“…The digital divide appears to contribute to gaps in educational and occupational opportunities, health awareness, access to health care services, and many other factors affecting health disparities 43,44 . In addition, discrimination in the criminal justice system and incarceration may further limit educational and employment opportunities for people of color 45‐47 . Care providers' implicit or explicit racial bias could also lead to substandard medical treatment 15 …”
Section: Factors That Contribute To Cancer Disparities Across the Can...mentioning
confidence: 99%